THE VIOLATION OF THE COOPERATION PRINCIPLE IN THE INTERACTION BETWEEN ADMINISTRATORS AND CUSTOMERS IN THE SIDESTOCK ONLINE STORE - Yasir Mubarok; Andi Ismayanto (PARADIGM: Journal of Language and Literary Studies, 2021)
This study aims to describe the form of speech between e-commerce administrators and customers and describe the violation of the principle of cooperation in the interaction between e-commerce administrators and customers. This study used the descriptive qualitative method. The object in this study is the speech between e-commerce administrators and customers in the form of chat. The data found are 23 data. It was obtained by using basic techniques in the form of reading chat conducted by admins and customers in terms of data collection, collecting library data sources and other data sources, and reading library data sources. The theoretical reference used to examine the data is by using Grice's pragmatic approach. The results showed that there is a violation of the principle of cooperation carried out by the speakers. They are a form of violation of the principle of cooperation; the maxim of quantity as many as 12 data, the maxim of relevance as much as 4 data, and the maxim of manner as many as 7 data. In this study, the most dominant violation of the cooperative principle is the maxim of quantity. In the interaction between e-commerce administrators and customers, there are many utterances involving sellers and buyers in bargaining for goods, so that many utterances spoken by admins exceed the information that customers need. In this case, the admin as the seller must offer the goods even though the customer does not need them in the context. In addition, the violation of the maxims is used to make their goods sell.